PENGARUH PELAYANAN PRIMA TERHADAP KEPUASAN NASABAH (STUDI KASUS DI PT. BANK JATIM CAPEM MARON PROBOLINGGO) - Deddy Junaedi (Nurul Jadid University, 2020)
This research is explanatory. The purpose of this study is (1) To analyze and determine the effect of service attitude aspects on customer satisfaction; (2) To analyze and determine the effect of service aspects Attention to customer satisfaction; (3) To analyze and determine the effect of service aspects of the Actions on customer satisfaction. The population in this study are customers who conduct financial transactions at Bank Jatim Capem Maron Probolinggo. Sampling at the time of the study using the method of accidental sampling took samples of anyone who was there or happened to be found when filling out the questionnaire. The results of this study are (1) Attitude has a significant and negative influence on Customer Satisfaction; (2) Attention has a significant and positive influence on Customer Satisfaction; (3) Action is the most dominant variable.